2019
DOI: 10.1371/journal.pgen.1007819
|View full text |Cite
|
Sign up to set email alerts
|

The complex architecture and epigenomic impact of plant T-DNA insertions

Abstract: The bacterium Agrobacterium tumefaciens has been the workhorse in plant genome engineering. Customized replacement of native tumor-inducing (Ti) plasmid elements enabled insertion of a sequence of interest called Transfer-DNA (T-DNA) into any plant genome. Although these transfer mechanisms are well understood, detailed understanding of structure and epigenomic status of insertion events was limited by current technologies. Here we applied two single-molecule technologies and analyzed Arabidopsis thaliana line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 61 publications
(88 reference statements)
6
127
0
Order By: Relevance
“…sequencing (Jupe et al, 2019) and represents to our knowledge the only publicly available line with an insertion in the TPK3 coding region. Subsequently, we isolated homozygous tpk3-1 (SALK_049593) individuals by PCR and confirmed a T-DNA insertion in the first exon by sequencing ( Fig.…”
Section: Tpk3 Loss or Gain Of Function Does Not Affect Photosyntheticmentioning
confidence: 99%
“…sequencing (Jupe et al, 2019) and represents to our knowledge the only publicly available line with an insertion in the TPK3 coding region. Subsequently, we isolated homozygous tpk3-1 (SALK_049593) individuals by PCR and confirmed a T-DNA insertion in the first exon by sequencing ( Fig.…”
Section: Tpk3 Loss or Gain Of Function Does Not Affect Photosyntheticmentioning
confidence: 99%
“…Read-lengths are limited only by input DNA lengths, and validated reads as long as 2,272,580 bases have been reported [2]. Nanopore sequencing has been used for various applications, including genome sequencing of Arabidopsis and a wild tomato relative [3, 4], resolving complex T-DNA insertions [5], and disease resistance gene enrichment sequencing [6].…”
Section: Introductionmentioning
confidence: 99%
“…We explored the coverage of this locus in our MethylC-seq data (data not shown) and found a 12.6-kb deletion present in the aly1-2 mutant line encompassing the six genes AT4G22285 to AT4G22310 (gene annotations provided in Supplemental Figure 4A). Deletions can occur during the process of transgenesis, which was used to generate the aly1-2 line (Nacry et al, 1998;Jupe et al, 2019). We found that this deletion did not cause the loss of RdDM phenotype in aly1-2, as the deletion was not present in the aly1-1 mutant line (Supplemental Figure 4B), which displays decreased RdDM ( Figures 1A and 1C).…”
Section: Aly1 Functions In Te Silencingmentioning
confidence: 66%